Risk of severe infection associated with immunoglobulin deficiency under rituximab therapy in immune-mediated inflammatory disease - Claire Rempenault; Bernard Combe; Jacques Morel; Philippe Guilpain; Cédric Lukas; Claire Immediato Daïen; Léa Tardivon (RMD Open)
Objectives We evaluated the risk of severe infection in patients with immune-mediated inflammatory disease (IMID) treated with RTX and with Ig deficiency.Methods This was an observational, retrospective single-centre study of patients undergoing treatment with at least one rituximab (RTX) infusion for an IMID until 31 May 2020. Patients were followed up for at least 12 months after the last infusion or until severe infection or death. Ig deficiency was classified as prevalent (before RTX) or acquired (normal Ig assay results before RTX but Ig deficiency during a follow-up).Results Of 311 patients, 10.6% had prevalent and 19.6% acquired Ig deficiency. Prevalent Ig deficiency was related to concomitant treatment with glucocorticoids (GCs), in particular with a high daily dose at baseline; and acquired Ig deficiency to cumulative dose of RTX, mean Disease Activity Score in 28 joints (DAS28), immunosuppressor or GCs therapy at baseline, diabetes mellitus and obesity. Overall, 14.5% of patients had a severe infection during follow-up, which was numerically but not statistically more frequent in patients with prevalent Ig deficiency than normal Ig level. On multivariate analysis, risk of severe infection was associated with chronic pulmonary disease, GCs dose and mean DAS28-C reactive protein. In a time-dependent analysis, risk of severe infection was not associated with Ig deficiency, either acquired or prevalent (adjusted HR 1.04 (95% CI 0.5 to 2.3), p=0.92).Conclusion Risk of severe infection was not associated with RTX-induced Ig deficiency in patients with an IMID. RTX management should be discussed according to an individual assessment of the infectious risk, especially in patients with GC therapy or chronic lung disease.